Enhancing Numeracy Literacy through Developing CBL-STEM Context Learning Materials with Interactive Video and Wordwall - Hutauruk, Stefany Margaretha; Ardiansyah, Adi Satrio (Jurnal Riset Pendidikan Matematika, 2026)
Numeracy literacy is important to have in order to face the challenges of the 21st century. In fact, the mastery of numeracy literacy in students in Indonesia is not optimal. In order to support the improvement of numeracy literacy, the development of learning materials is needed. The purpose of this research is to develop CBL-STEM Context learning materials integrated with Interactive video and Wordwall to improve numeracy literacy. This research uses the Research and Development (R&D) method with the 4D model. The data collection techniques used were interviews, tests and questionnaires. Data analysis techniques used quantitative descriptive analysis techniques with several statistical tests such as one sample t-test, independent sample t-test, dependent sample t-tests, and z-test. he results of this study show that CBL-STEM Context learning materials integrated with Interactive video and Wordwalls get an average percentage score of feasibility, readability and learner responses of 93.30%, 92.16%, and 97.22% respectively and effectively improve numeracy literacy. Based on the results of this study, learning materials can be used as learning resources that effectively improve numeracy literacy.